Philosophical Perspectives on Bioethics - Boyle, Joseph (Book collections on Project MUSE., 1996)
The contributors to the volume discuss various approaches to bioethical thinking and the political and institutional contexts of bioethics, addressing underlying concerns about the purposes of its practice.